MAQOL TIL VA NUTQ BIRLIGI SIFATIDA («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article examines French proverbs from a paremiological point of view.In particular, their communicative and pragmatic functions as a linguistic and speech unit, as well as cultural and ethnic problems are considered. Also, the pragmatic properties of proverbs are revealed linguistically in accordance with their unambiguity in the form of a sentence, different significance in a situational context.
Keywords: proverb, paremiology, communicative and pragmatic function, cultural and ethnic task, unity of language and speech.